Spatial-temporal agricultural production of Citrus x limon and Mangifera indica, using spectral signatures and satellite images (Scientia Agropecuaria, 2021)
Agricultural production of Citrus x limon (lemon) and Mangifera indica (mango) in the Piura region is often affected by environmental-climatic factors, mainly by possible seasonal changes or extreme weather events, such as droughts or El Niño. The objective is to analyze the spatial-temporal agricultural production of lemon and mango, measuring with the FieldSpec4 spectroradiometer, the spectral signature (SF) and Sentinel 2 satellite images (ISS2) of the Chulucanas criollo mango in crops of Pampa Larga-Alvarados-Suyo-Ayabaca and INIA-Hualtaco-Tambogrande-Piura mango germplasm bank, respectively. The method consists of entering each EF in the ISS2 (2019) mosaic of tiles 17MMR-17MNR-17MPR-17MMQ-17MNQ-17MPQ-17MMP-17MMP-17MNP-17MPP, using SEN2COR280 in SNAP software. The time series of monthly/annual production of lemon and mango were analyzed using data from INEI and SIEA-MIDAGRI-PERU. The results obtained estimate a lemon cultivated area of 27 451.84 ha and mango cultivated area of 22000 ha; higher than the reported harvested area of 16113 ha and 20606 ha, respectively. Mango production 1970-2020, is higher in November-December-January-February, explained by the harvested area in 84.1%, showing seasonality, exponential growth behavior and positive (2003-2020) and negative (1970-2002) anomalies. Monthly lemon production 2007-2020 is seasonal, the annual trend increases by 2.8% despite the existence of negative anomalies in 2017, generated by the effects of the "Coastal El Niño" in its evolutionary flowering process, forecasting improvement in lemon production in Piura, between 2021 and 2022.
Keywords: Agricultural production; Citrus x limon; Mangifera indica; Spectral signature; Spatial-temporal distribution; Anomalies